Esemephe peba sp. nov., the first Brazilian Esemephina (Coleoptera: Tenebrionidae: Cossyphodini) - Aloquio, Sergio; Grossi, Paschoal Coelho; Lopes-Andrade, Cristiano (Zootaxa, 2019)
Esemephe peba sp. nov is described. This newly discovered species represents the first record of Cossyphodini from Brazil. It is also the second species of the genus Esemephe Steiner and differs from the type species in antennal, elytral and aedeagal structure. Descriptions of male and female terminalia are provided, as well as the revised diagnosis and distributional map for Esemephina. Finally, an updated identification key to the World genera of Cossyphodini is proposed.